How intravenous iron therapy affects arrhythmia burden and functional status in patients with advanced heart failure and implantable devices. (14th October 2021) - Mouselimis, D; Tsarouchas, A; Bakogiannis, C; Mitsas, A; Tsalikakis, D; Tsavousoglou, C; Vergopoulos, S; Kelemanis, I; Theofillogiannakos, E.K; Antoniadis, A.P; Tzikas, S; Fragakis, N; et al.
Abstract: Background: Heart failure with reduced ejection fraction (HFrEF) is a disease that confers significant morbidity and mortality to patients. Patients suffer from increased arrhythmia burden; lethal ventricular arrhythmias are frequent. Iron deficiency (ID) is increasingly recognized as a common comorbidity that constitutes a further detriment to patients' cardiorespiratory capacity and an independent prognosticator of mortality. ID treatment with intravenous ferric carboxymaltose (IV FCM) has proven beneficial, improving QoL and exercise capacity in HFrEF patients with ID. Iron depletion is linked to disturbed myocyte electromechanical balance, especially in HF. However, the role of IV FCM arrhythmic burden in HFrEF patients with ID has not been examined. Purpose: Investigate the effect of IV FCM treatment on the functional capacity, QoL and arrhythmic burden of in HFrEF patients with ID and cardiac implantable electronic devices (CIED). Methods: HFrEF patients with ID and CIEDs were recruited from our outpatient HF clinic. CIED telemetry revealed their arrhythmic burden for the 6 months preceding IV FCM administration. Patients underwent physical examination, blood testing, 6-minute walk testing, 24-hour Holter monitoring, QoL quantification with the KCCQ and EQ-5D-5L questionnaires and repeat CIED telemetry at study baseline (IV FCM administration) and 6-months. Microvolt T-wave alternans (MTWA) and heart rate turbulence (HRT) slope and onset were quantified through the 24-hour ECG recordings. HRT results are reported as HRT0, HRT1 or HRT2 based on the number of abnormal HRT parameters. Results: So far, 83 (aged 68.3±8.7 years, 82% male) out of a total of 96 recruited patients have completed the 6-month follow-up (3 of 83 died before the 6-month mark). Picture 1 contains patients' baseline characteristics and 6-month results. Patients received a mean of 1.43±0.61g of IV FCM during the follow-up period, which significantly ameliorated iron status (Picture 1). The 6MWD increased by 32.4m (95% CI: 14.7–47.2, P<0.001), as did the KCCQ total score (P=0.008). Patients' CIEDs recorded significantly more nsVTs in the 6 months preceding IV FCM administration (2.2±15.7 per month) opposed to the subsequent period (0.06±3.1 per month, P=0.006). Patients' MTWA improved at 6-months over baseline (P=0.004), and a trend for improvement in HRT scores was observed (P=0.06). Hospitalization-free survival curves of these time periods reveal a non-significant trend for lower hospitalization risk following IV FCM (HR=1.9, P=0.09). Conclusions: After 6 months of IV FCM treatment, HFrEF patients with ID had significantly better exercise capacity and quality of life. Regarding arrhythmias, a tentative improvement in CIED- and Holter-derived arrhythmic markers was observed. Extended follow-up of a larger sample size will provide further insight for the effect of IV FCM in these patients' arrhythmic burden. Funding Acknowledgement: Type of funding sources: None.